EFEKTIVITAS PENGGUNAAN WEBSITE DESA TERHADAP KINERJA APARATUR DESA KEMILI KECAMATAN BEBBESAN KABUPATEN ACEH TENGAH - Latea, Cut Salsabillah Mudmainah; Hamdani, Hamdani; Amri, Mustika (Ekonis: Jurnal Ekonomi dan Bisnis, 2025)
Abstract:  This study evaluates the effectiveness of using the Kemili Village website on the performance of village officials. The aim is to determine the extent to which the village website affects the performance of the Kemili Village apparatus, Bebesen District, Central Aceh Regency. The results of the study are expected to provide insight and evaluation of the management of village websites to meet the needs of the community.This research was conducted in Kemili Village, Bebesen District, Central Aceh Regency with a focus on the effectiveness of the use of village websites on the performance of village officials. The study population was 1,461 people, with a sample of 94 people taken using purposive sampling method. Primary data were collected through questionnaires. Data analysis techniques include simple linear regression analysis, validity, reliability, and classical assumption tests. t test results show a significant positive effect (5.024, p 0.05) with an R Square of 21.5%, indicating that although the village website has a positive effect, many other factors affect the performance of the apparatus. The main obstacle is incomplete information. Based on the results of the study, it is recommended that village officials improve the effectiveness of the village website by updating information regularly, conducting socialization to the community about the benefits and how to use the website, and collecting feedback through surveys or discussion forums.  Keywords: Village Website Effectiveness, Village Apparatus Performance, and Community Satisfaction.